Vacuolar sequestration of glutathione S-conjugates outcompetes a possible degradation of the glutathione moiety by phytochelatin synthase - Grzam, Anke; Tennstedt, Pierre; Clemens, Stephan; Hell, Rüdiger; Meyer, Andreas (FEBS letters, 2006)
Monochlorobimane was used as a model xenobiotic for Arabidopsis to directly monitor the compartmentation of glutathione-bimane conjugates in situ and to quantify degradation intermediates in vitro. Vacuolar sequestration of the conjugate was very fast and outcompeted carboxypeptidation to the γ-glutamylcysteine-bimane intermediate (γ-EC-B) by phytochelatin synthase (PCS) in the cytosol. Following vacuolar sequestration, degradation proceeded to cysteine-bimane without intermediate. Only co-infiltration of monochlorobimane with Cd2+ and Cu2+ increased γ-EC-B formation to 4% and 25%, respectively, within 60 min. The role of PCS under simultaneous heavy metal stress was confirmed by investigation of different pcs1 null-mutants. In the absence of elevated heavy metal concentrations glutathione-conjugates are therefore first sequestered to the vacuole and subsequently degraded with the initial breakdown step being rate-limiting.